0773 Familial Factors Associated With Sleep Patterns At Age 1 Year In The ELFE Birth-Cohort. (12th April 2019) - Messayke, Sabine; Franco, Patricia; Forhan, Anne; Dufourg, Marie-Noëlle N; Charles, Marie-Aline A; Plancoulaine, Sabine
Abstract: Introduction: Infant sleep plays a critical role in his/her normal development. Sleep problems, including sleep onset difficulties (SOD) and night waking (NW), in infants and young children ranges from 20% to 30% and were found to be partially persistent over time up to adulthood. In USA and UK, lower incomes and educational level as well as some racial/ethnic groups have been positively associated with children sleep problems. Few studies focused on infants. We here aimed at studying associations between familial characteristics and sleep patterns in 1-year-old infants from the French nationwide ELFE birth-cohort Methods: This study included 11, 468 infants from the birth-cohort with information on both sleep (duration/24h (TST), SOD and NW/week) at age 1 and familial factors (parental birthplace, duration since migration to France, single parenting, home crowding index, income per consumption unit, maternal education and working schedule, main childcare). Associations were studied using multinomial logistic regressions adjusted for maternal and infant's characteristics including health, sleep habits. Results: Mean TST was 13hrs36 including 2hrs54 of naps, 25% of the infants had TST less than 13hrs/24h and 9.3% &ge16hrs/24h. About 46% did not present SOD or NW, while 15.8% had often SOD and 22.3% NW&gt1 night over 2. Crowding index was positively associated with short sleep duration (&lt13h/24h) and negatively with longer sleep duration (&gt14hrs/24h) compared to 13-14h/24h as were migration duration &lt10 years and community and nursery assistant childcare at age 1. Low educational levels were positively associated with TST&lt11hrs/24h and intermediate levels with TST&ge16hrs/24h compared to high levels. Community and nursery assistant childcare at age 1 year were positively associated 1-to-2 NW/week. Single parenting and being a full-time working mother were negatively associated with NW whatever the frequencies while being part-time working was positively associated with SOD. Incomes or parental birthplace were not associated with infant sleep patterns. Conclusion: Several familial factors, reflecting socioeconomic and sociocultural environment, were associated with infants sleep patterns as early as 1 year old in France. Study of associations' persistence over time would be interesting. Support (If Any): N/A